Platformization of Media Entrepreneurship: A Conceptual Development - Dal Zotto, Cinzia; Omidi, Afshin (Nordic Journal of Media Management, 2020)
Purpose: Platformization is one of the most insightful theoretical frameworks which has an exceptional potential to provide a fine-grained ground for understanding the digital platforms' overall contributions to develop different research fields. Despite the significant role of digital platforms in developing the field of 'media entrepreneurship,' a systematic attempt to make sense of the field by using the platformization framework is scarce. The present paper, therefore, seeks to (re)reading the field of ‘media entrepreneurship” by employing the platformization framework. Methodology: By adopting the platformization framework, the paper has reorganized the extant literature to shed some light on how the field of media entrepreneurship is multi-faceted and intertwined with a vast array of societal concerns in the age of digital platforms. Findings/Contribution: The investigations in this study corroborate the idea that media entrepreneurs should be equipped with a multi-paradigmatic lens to see how their practices may have beneficial implications for the media industries, and they can also engage in some unfair and monopolistic initiatives that are prompted by the platforms and also by governmental interventions. The platformization framework, introduced and developed in this research, reveals its potential as insightful perspective to systematically move the field of media entrepreneurship forward, from theory to practice.